Daily physical activity and alcohol use across the adult lifespan - Conroy, D.; Ram, N.; Pincus, A.; Coffman, D.; Lorek, A.; Rebar, Amanda; Roche, M. (American Psychological Association, 2015)
© 2014 American Psychological Association. Objective: In contrast to proposals that physical activity (PA) can be a substitute for alcohol use, people who engage in greater overall PA generally consume more alcohol on average than less-active peers. Acknowledging that both PA and alcohol use vary considerably from day-to-day, this study evaluated whether established associations reflect daily behavioral coupling within-person, are an artifact of procedures that aggregate behavior over time, or both. Methods: A life span sample of 150 adults (aged 19-89 years) completed three 21-day measurement bursts of a daily diary study. At the end of each day, they reported on their PA and alcohol consumption. Data were analyzed in a negative binomial multilevel regression. Results: As expected, both behaviors exhibited limited between-person variation. After controlling for age, gender, and seasonal and social calendar influences, daily deviations in PA were significantly associated with daily total alcohol use. Once the within-person process linking PA and alcohol use was controlled, usual PA and total alcohol use were not associated. Conclusions: The established between-person association linking PA and alcohol use reflects the aggregation of a daily process that unfolds within-people over time. Further work is needed to identify mediators of this daily association and to evaluate causality, as well as to investigate these relations in high-risk samples.